The branching ratio of intercombination A1Σ+∼b3Π→a3Σ+/X1Σ+transitions in the RbCs molecule: Measurements and calculations. (November 2020) - Krumins, V.; Kruzins, A.; Tamanis, M.; Ferber, R.; Pashov, A.; Oleynichenko, A.V.; Zaitsevskii, A.; Pazyuk, E.A.; Stolyarov, A.V.
Highlights: The detection of the exremely weak A 1 S i g m a + b ˜ 3 P i → a 3 S i g m a transitions in laser-induced fluorescence of RbCs. The scalar- and full-relativistic ab initio calculations of the transition dipole moments. The comparison of the experimental and theoretical branching ratios of transitions to the triplet and singlet ground states. The explanation of pecularities in the doublet progressions to the triplet ground state. Abstract: We observed the A 1 Σ + ∼ b 3 Π → a 3 Σ + / X 1 Σ + laser-induced fluorescence (LIF) of the RbCs molecule excited from the ground X 1 Σ + state by the Ti:Sapphire laser. The LIF spectra from the common perturbed levels of the singlet-triplet A ∼ b complex was recorded by the Fourier-transform (FT) spectrometer with the instrumental resolution of 0.03 cm − 1 . The relative intensity distribution in the rotationally resolved A ∼ b → a 3 Σ + ( v a ) / X 1 Σ + ( v X ) progressions was measured, and their branching ratio was found to be about of 1 ÷ 5 × 10 − 4 in the bound region of the a 3 Σ + and X 1 Σ + states. The experiment was complemented with the scalar- and full-relativistic calculations of the A / b − X / a transition dipole moments (TDMs) as functions of internuclear distance. The relative systematic error in the resulting ab initio TDM functions evaluated for the strong A − X transition was estimated as few percent in the energy region, where the experimental LIF intensities are relevant. The relative spectral sensitivity of the FT registration system, operated with the InGaAs diode detector and CaF beam-splitter, was calibrated in the range [6 500, 12 000] cm − 1 by a comparison of experimental intensities in the long A ∼ b → X ( vX ) LIF progressions of the K2 and KCs molecules with their theoretical counterparts evaluated using the ab initio A − X TDMs. Both experimental and theoretical transition probabilities can be employed to improve the stimulated Raman adiabatic passage process, a → A ∼ b → X, which is exploited for a laser assembling of ultracold RbCs molecules.